Palisaded Encapsulated Neuroma of the Tongue Clinically Mimicking a Pyogenic Granuloma: A Case Report and Review of Literature - Nazanin Mortazavi; Azadeh Gholami; Pouyan Amini Shakib; Hamed Hosseinkazemi (Tehran University of Medical Sciences, 2016)
Palisaded encapsulated (solitary circumscribed) neuromas (PENs) are relatively common intraoral neurogenic tumors, which occur most frequently on the hard palate. Herein, we describe the clinicopathological characteristics of a palisaded encapsulated neuroma of the tongue. This tumor was an exophytic sessile mass measuring 0.3× 0.4 cm with rubbery consistency on the anterior one-third of the dorsum of the tongue. The tumor was excised under the impression of a pyogenic granuloma (PG). No recurrence was reported at 12 months postoperatively. Histopathological examination showed a well-circumscribed mass that composed of interlacing fascicles of spindle cells. The cells were S-100 positive. The nuclei, showing parallel orientation within the fascicles, were wavy and pointed and showed no sign of mitotic activity. Giemsa staining revealed no mast cells within the stroma.